IGBT-SiC dual fed ground power unit - Rovere, Luca; Formentini, Andrea; Lo Calzo, Giovanni; Zanchetta, Pericle; Cassia, Andrea; Marchesoni, Mario (2017)
This paper presents the design and control of a three-phase ground power supply unit for aircraft servicing. A new mixed technology converter composed by a three-phase Silicon Carbide (SiC) full bridge unit and a three-phase full bridge IGBT unit connected across the same dc link is used instead of the conventional full bridge configuration. In order to satisfy the stringent requirements of the output voltage quality particular attention is given to the controller. The common dc link topology of the converter allows circulation of Zero Sequence Current (ZSC), therefore also a 0 axis regulator is necessary. The state space model of the system considering the LC output filter is presented and used in order to synthetize the controller parameters using the Optimal Control theory.